THE FIELD OF DIDACTICS - Costa, Patricia Silvana Peratto (Seven Editora, 2025)
Didactics concerns with teaching and learning strategies together. The strategies of teaching refer to the design, programming, elaboration and formulation of learning contents in a verbal or written form (W. Casasola, 2020). We present different didactic strategies related with teaching and learning processes. This work, offers a summary of the study and reflexion about different definitions of didactics that have appeared along the time. Describes a frame of basic knowledge about an issue that attempts to be an invitation for research, analysis, reflexion and applicability of didactics to a formative scope of any level. We present definitions for didactics from its beginning to the more recent approachs. The field of Didactics has evolved from Comenio, Classical Didactics, Critical Didactics, inside the Critical from Traditional, Cognotivist, New Dimension Didactics. Besides this we present the importance of Time in Teachable Moment, the Human Development, Didactical Research, Didactics and Curriculum, Applied Didactics, Constructivism, Modern Didactics, Universitary Didactics, Contemporary Didactics and Competencies. DOI: https://doi.org/10.56238/sevened2025.030-082